HIGHLY EFFECTIVE THERMOMECHANICALY REINFORCED REBAR - Vakulenko, I. O.; Razdobreiev, V. H.; Perkov, O. M. (Science and Transport Progress, 2007)
The article investigates the structure, mechanical and services characteristics of high-strength rebar, thermomechanically strengthened under different cooling modes.